Effect of carbohydrates on adherence of Escherichica coli to human urinary tract epithelial cells. - Schaeffer, A J (1980)
Adherence of Escherichia coli cells to voided uroepithelial cells from healthy women was measured by use of [3H]uridine-labeled bacteria filtered through a polycarbonate membrane filter (5-micrometer pore size). At a concentration of 2.5% (wt/vol), D-mannose, D-mannitol, alpha-methyl-D-mannoside, and yeast mannan completely inhibited adherence of the bacteria to the epithelial cells. At this same concentration, D-fructose, D-lyxose, D-arabinose, and D-glyceraldehyde partially inhibited adherence. Reducing the concentration of D-mannose, or its derivatives, to between 1.0 and 0.1% resulted in partial inhibition in the adherence of the bacteria; a further reduction in the concentration to between 0.01 and 0.001% caused an enhancement of adherence up to 160% of the control level. Bacterial preincubation in 2.5% D-mannose for 1 min before epithelial cells were added completely inhibited adherence; similar treatment of the epithelial cells had no significant effect on subsequent adherence of the bacteria. Bacteria that were preincubated for 1 h with D-mannose at concentrations between 0.1 and 0.75% showed enhanced adherence. The inhibitory effect of D-mannose was decreased if bacterial adhesive ability, or cell receptivity, increased. A variety of other carbohydrates tested had no effect on the adherence of E. coli to the uroepithelial cells. These results suggest that adherence can be altered by interaction(s) between specific carbohydrate molecules and receptors on the bacterial surface.